EKSISTENSI REKONSTRUKSI DALAM PEMBUKTIAN PERKARA PIDANA - Silaen, Merry Chrystin (Katalogis, 2015)
The reconstruction results shall be stated in reconstruction report completed with photos of acts demonstrated during the reconstruction. The photos pertaining to be integral parts and inseparable from reconstruction report are often adopted by the investigators to investigate certains crimes. The research question was how reconstruction existence in a criminal case could support evidences contained a police investigation report and what their hindrances were. The research was supposed to identify the capacity of reconstructions in a criminal case to strengthen crime evidences declared in a police investigation report was and their hindrances were. It was socio-legal research , i.e.:a legal and non legal oriented research to study the mechanisme of both legal and non legal aspect in the society. The reconstructions detailed in the reconstruction report shall serve as supplements to complete a police a police investigations report certains criminal cases to disclose material truths in a crime proofing as basis for sentencing a verdict. The hindrances arise when reconstruction are based on result of presumption from unprovable material truth resources of investigation, instead of evidences factually found in an investigation.